2001
DOI: 10.1093/toxsci/64.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Profiles in Fetal Rat Testes after in Utero Exposure to Di(n-butyl) Phthalate

Abstract: Di(n-butyl) phthalate (DBP) has antiandrogenic-like effects on the developing reproductive tract in the male rat and produces regions of interstitial cell hyperplasia and gonocyte degeneration in the developing fetal testes at maternal doses of 100-500 mg/kg/day. Neither DBP nor its primary metabolites interact with the androgen receptor in vitro. The present study was performed to examine gene expression in the fetal rat testes following in utero DBP exposure. Pregnant Sprague-Dawley rats received corn oil, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
132
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 45 publications
15
132
1
Order By: Relevance
“…These abnormalities are consistent with inhibiting fetal testosterone production (Scott et al, 2009). Moreover, decreases in testicular or serum testosterone levels in juvenile male rats (≤ postnatal days 35) (Shultz et al, 2001;Mylchreest et al, 2002;Fisher et al, 2003;Fisher, 2004) and in adult male rats Wakui et al, 2013Wakui et al, , 2014Giribabu et al, 2014) were described after in utero DBP exposure. Leydig cells (LC) are the cells that synthesize testosterone.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…These abnormalities are consistent with inhibiting fetal testosterone production (Scott et al, 2009). Moreover, decreases in testicular or serum testosterone levels in juvenile male rats (≤ postnatal days 35) (Shultz et al, 2001;Mylchreest et al, 2002;Fisher et al, 2003;Fisher, 2004) and in adult male rats Wakui et al, 2013Wakui et al, , 2014Giribabu et al, 2014) were described after in utero DBP exposure. Leydig cells (LC) are the cells that synthesize testosterone.…”
Section: Introductionsupporting
confidence: 58%
“…In addition, in the fetal testis after treatment with DBP, it has been reported that reduction in fetal testicular testosterone levels occurs via several steroidogenesis enzymes/associated genes and proteins: SR-B1, StAR, P450scc, 3β-hydroxysteroid dehydrogenase/Δ 5-4 isomerase (3β-HSD), steroid 17 alpha-hydroxylase/17,20 lyase (P450c17), and 17β-Hydroxysteroid dehydrogenases (17β-HSD) Shultz et al, 2001;Barlow and Foster, 2003;Thompson et al, 2004). In the present study, the testosterone levels observed in the 100 mg DBP dose group were significantly lower than all other dose groups at all time-points investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Before proceeding to discriminant and pathway analyses on these newly identified proteins, we probed western blots of extracts from control and DEHP-exposed testes with P450scc (CYP11A1) to confirm the absence of altered expression at both 10 and 100 mg exposures. This protein was selected, as several studies have demonstrated decreased gene expression of P450scc and other steroidogenic molecules following in utero exposure to phthalates at doses as low as 100 mg (Shultz et al 2001, Lehmann et al 2004, Hannas et al 2011. We observed no decrease across the DEHP exposures; a slight decrease at 100 mg was suggested.…”
Section: Biomarkers Of Dysgenesis In Fetal Rat Testismentioning
confidence: 55%
“…In general, the expression of P450scc and P450c17 is not significantly altered until relatively high doses of phthalates are administered (500 mg DBP/kg; Shultz et al (2001) and Lehmann et al (2004)) whereas StAR's gene expression decreased at 50 mg DBP/kg (Lehmann et al 2004) and 100 mg DEHP/kg (Borch et al 2006). The importance of the posttranscriptional products (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…NA MICROARRAYS have been widely used for the discovery of the altered profiles of gene expression associated with toxicity and disease (Lander et al, 2001;Shultz et al, 2001;Yeoh et al, 2002), including many cancers (Khan et al, 2001;Perou et al, 2000;Shi et al, 2005c;Sorlie et al, 2001;Tothill et al, 2005;van 't Veer et al, 2002;Yeoh et al, 2002). Microarrays are commonly employed for identifying genes with expression differences in transcript concentrations between the sample classes (e.g., from diseased versus healthy tissue).…”
Section: Introduction Dmentioning
confidence: 99%